2016
DOI: 10.1002/cncr.30028
|View full text |Cite
|
Sign up to set email alerts
|

Change in chemotherapy during concurrent radiation followed by surgery after a suboptimal positron emission tomography response to induction chemotherapy improves outcomes for locally advanced esophageal adenocarcinoma

Abstract: Background PET scan after induction chemotherapy before pre-operative chemoradiation and surgery for esophageal adenocarcinoma predicts outcomes. Some patients with progression on PET after induction chemotherapy had long-term overall survival (OS) when changed to alternative chemotherapy during radiation. Patients and methods We retrospectively reviewed esophageal adenocarcinoma patients who received induction chemotherapy and chemoradiation prior to planned surgery; all had PET scan before and after induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Preliminary results showed a pCR rate of 17% and 19% in PET nonresponders who changed from carboplatin to FOLFOX and from FOLFOX to carboplatin/ paclitaxel respectively, compared to a historic rate of 3% in a retrospective analysis performed at MSK. 19 Furthermore, median OS was 47.3 months in PET responders versus 28.9 months in PET nonresponders (p ¼ 0.09). 10 Based on comparison with historic controls, changing chemotherapy in PET nonresponders appears to improve survival in this patient population.…”
Section: Discussionmentioning
confidence: 94%
“…Preliminary results showed a pCR rate of 17% and 19% in PET nonresponders who changed from carboplatin to FOLFOX and from FOLFOX to carboplatin/ paclitaxel respectively, compared to a historic rate of 3% in a retrospective analysis performed at MSK. 19 Furthermore, median OS was 47.3 months in PET responders versus 28.9 months in PET nonresponders (p ¼ 0.09). 10 Based on comparison with historic controls, changing chemotherapy in PET nonresponders appears to improve survival in this patient population.…”
Section: Discussionmentioning
confidence: 94%
“…2,8 The applicability of an interim positron emission tomography (PET) scan with 18 F-fluorodeoxyglucose (FDG) to measure response to CRT is of limited use with current standard PET parameters, especially in ESCC, 9 although PET-tailored treatment has shown some promising results in adenocarcinomas of the esophagus. 10 Currently, the most often investigated FDG-PET/CT parameter is tumor glucose uptake quantified as standardized uptake value (SUV). However, SUV quantification has several wellknown shortcomings, for example, uptake time dependence of the SUV, interstudy variability of the arterial input function and susceptibility to errors in scanner calibration.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of an interim positron emission tomography (PET) scan with 18 F‐fluorodeoxyglucose (FDG) to measure response to CRT is of limited use with current standard PET parameters, especially in ESCC, although PET‐tailored treatment has shown some promising results in adenocarcinomas of the esophagus …”
Section: Introductionmentioning
confidence: 99%
“…Changing the chemotherapy regimen during radiation for 18 F-FDG PET nonresponders might also be effective. Ku et al reported that patients who did not respond on 18 F-FDG PET after induction chemotherapy and whose chemotherapy was changed during the chemoradiotherapy had significantly better PFS than did patients whose chemotherapy regimen was not changed (14). On the other hand, whether nonresponders can proceed directly to surgery is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that 18 F-FDG PET response after induction chemotherapy could predict pathologic complete response (pCR) and was associated with survival outcomes in esophageal cancer patients treated with induction chemotherapy followed by neoadjuvant or definitive chemoradiotherapy (11)(12)(13). Moreover, an early 18 F-FDG PET response could provide useful information for choosing a chemotherapy regimen to be used during radiation for those who do not show an 18 F-FDG PET response (14). However, the value of 18 F-FDG PET response after induction chemotherapy in terms of identifying which patients will benefit from subsequent surgery after chemoradiotherapy has never, to our knowledge, been investigated.…”
mentioning
confidence: 99%